Assessment of status and threats of wild mammals in some selected locations of Dinajpur district, Bangladesh - Haque, Md Amdadul; Khan, M Monirul H; Kabir, Md Mofizul (Jahangirnagar University Journal of Biological Sciences, 2021)
The status of mammals in Dinajpur district was studied from October 2016 to November 2017. For inventory and assessment of wild mammal’s belt-transect sampling, box trap survey, mist netting, night survey and questionnaire survey methods were used. A total of 22 species of mammals belonging to 11 families and 5 orders were recorded. Of the recorded species 8 were rodents, 1 hare, 1 shrew, 7 bats and 5 carnivores. Muridae appeared as the largest family containing 8 species. A total of 9 species (41%) were recorded as “very common”, 6 species (27%) “common”, 4 species (18%) “uncommon”, and 3 species (14%) “rare”. Among all the mammalian species, 41% (9 species) were nocturnal, 14% (3 species) crepuscular, 37% (8 species) metaturnal and 9% (2 species) diurnal. On the other hand, 55% (12 species) of mammals were terrestrial, 9% (2 species) arboreal, 32% (7 species) aerial and 4% (1 species) aquatic mammals. Of all the recorded species, 32% (7 species) were herbivores followed by 27% (6 species) carnivores, 5% (1 species) opportunists while frugivores and insectivores were 18% (4 species) each. About 19% (4 species) of the known species are nationally threatened comprising of Endangered (5%), Vulnerable (5%) and Near Threatened (9%) and Least Concern (81%). Based on the habitats, 14 species (64%) were recorded from forests, 7 (31%) from homestead vegetation’s and 1 (5%) species from wetlands. A good number of individuals (n=12) of the nationally threatened Bengal Fox (Vulpes bengalensis) were found in the study area and two mammal species, Indian Hare (Lepus nigricollis) and Large Indian Civet (Viverra zibetha) have been locally facing the threat of extirpation. The mammalian diversity in the natural forests (64%) was higher than that of the other habitats. Different anthropogenic threats, especially hunting by ethnic Santal people (frequency of observation 24 times, impact point 4), exist in the study area. The major proposed actions for the study area are habitat restoration, increase public awareness and conflict management. Jahangirnagar University J. Biol. Sci. 9(1 & 2): 21-34, 2020 (June & December)